Serum Uric Acid to Creatinine Ratio with Estimated Glomerular Filtration Rate in Type 2 Diabetes Patients - Baral, Sushil; Uprety, Ananta Bhakta; Kshetri , Rupesh (Journal of Nepal Health Research Council, 2023)
Background: Diabetes mellitus is a metabolic disorder associated with cardiovascular and renal complications. The serum uric acid to creatinine ratio and estimated glomerular filtration rate are important markers used to assess kidney function in patients with type 2 diabetes. This study aimed to find the correlation between serum uric acid to creatinine ratio and estimated glomerular filtration rate to various parameters among the diabetes patients.Methods: It is an observational hospital-based, cross-sectional study. Patients with a diagnosis of diabetes for three years or more duration were selected. This study designed to serum uric acid to creatinine ratio with estimated glomerular filtration rate and its relationship with other biochemical parameters. The Modification of Diet in Renal Disease formula was used to calculate estimated glomerular filtration rate (eGFR). eGFR (mL/min?1.73?m2)?=?186?×?(Scr) –1.154?×?(age) – 0.203?×?(0.742 female). Low eGFR was defined as eGFR<60 mL/min?1.73?m2. The data were analyzed by SPSS version 20. Mean values of different variables, standard deviations and p-values were calculated. Results: Mean serum uric acid to creatinine ratio was 6.09±1.71 and elevated among 49.1%. Mean blood urea and serum creatinine levels were 28.0±10.72 and 1.01±0.18, respectively. There was a significant positive correlation between eGFR and serum uric acid : serum creatinine ( r?=?0.246, p?=?0.007) in this study.Conclusions: The serum uric acid to creatinine ratio can serve as an early marker for renal injury, showing a positive correlation with estimated glomerular filtration rate (eGFR). Monitoring serum uric acid to creatinine ratio levels alongside eGFR can assistance in the identification and management of kidney damage in its early stages.Keywords: Creatinine; glomerular filtration rate; glycated hemoglobin; serum uric acid; type 2 diabetes